Financial reporting as indicator of financial management of enterprise (Journal of Economic Research & Business Administration, 2017)
The financial reporting is examined as an interlink between an enterpriseand his users. From предстaвленойin the financial reporting of information,the future of enterprise depends. In a management an enterprisethe system of indicators is by the system the second order, along with thesystem of instruments entering in the complement of the system of indicativemanagement. Indicator it is qualitatively-quantitative description ofthe examined process or phenomenon. He shows a change in a dynamicsor deviation from a normative value. In the strategic management ofactivity of enterprise the most well-known system of indexes is the Balancedsystem of indexes of Нортонa-Кaплaнa (BSC). BSC unites financialand unfinancial indicators. BSC contains having a special purpose indexeswrap-round all strategically important spheres of activity of organization;forms причинно-следственныеconnections between all groups of indexes;serves as an instrument for realization of strategies of organization andincrease of dataware of acceptance of administrative decisions; forms indicatorsfor a management by organization and т. of п. BSC foremost createdfor the leaders of higher level of management and owners of enterprises.